Virtual training on pumping stations for drinking water supply systems. - Romo Cunalata, Juan Esteban (2019)
This article offers the development of a realistic and intuitive virtual environment for training on pumping stations for drinking water supply systems. The environment has structures and equipment found in pumping stations that simplify the user interaction with the industrial process, instrumentation, monitoring and control of the station. The environment has been created using photogrammetry techniques, CAD tools and the UNITY 3D graphic engine that combined with MATLAB exchanges information in real time to execute the simulation of the process, achieving a high degree of realistic immersion. Experimental tests allow the operator to interact with the virtual environment and achieve maximum experience in the integrated station. Through experimental tests, the immersion of the training environment system is verified.